Ontological-Societal Security Node as a Phenomenon of the Digital Environment - Oxana I. Elkhova (RUDN Journal of Philosophy)
This study is dedicated to the conceptualization of the phenomenon of the ontological-societal security node in the context of the digital environment. The author demonstrates how the rapid development of digital technologies transforms the mechanisms of social integration, necessitating a reconsideration of traditional security approaches. In this context, the research analyzes the processes of interpenetration between ontological and societal security, driven by technological transformations. The research presents an original structural model of the ontological-societal security node, comprising three interrelated components: ontological, societal, and temporal. The ontological aspect includes identity, trust, and existential stability; the societal aspect encompasses collective identity, social ties, and institutional norms; the temporal aspect reveals historical continuity, transformation dynamics, and the degree of future predictability. The proposed model serves as an effective tool for studying digital risks, including identity fragmentation, social disintegration, and the influence of algorithmic systems on behavioral norms. The study highlights that digitalization not only accelerates the evolution of social structures but also intensifies their interdependence, forming a complex system of interactions between ontological and societal security. Information technologies permeate all aspects of the ontological-societal security node, reshaping identity, trust, social ties, and institutional norms. They blur the boundaries between the personal and the public, accelerate transformation processes, generate temporal disruptions, and alter the dynamics of social interactions. Network algorithms create information bubbles, affecting collective memory, future predictability, and mechanisms for managing digital risks, thereby exacerbating societal fragmentation. Incorporating the temporal component into the model allows for consideration of historical continuity, the pace of change, and the degree of future predictability, which play a crucial role in the adaptation of social systems to the challenges of the digital age. This research holds both scientific and practical significance by offering a novel methodological approach to analyzing digital security. The concept of the ontological-societal security node opens new prospects for further studies and can be applied in the development of strategies for societal adaptation to technological challenges.